2021
DOI: 10.1590/2179-8087-floram-2021-0040
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physicochemical Properties of Termite Mounds in the Mixed Deciduous Forests of Thailand

Abstract: In this study, we surveyed termites in Thailand and characterized the mounds they built in mixed deciduous forests. We analyzed soil samples from termite mounds for moisture, electrical conductivity, temperature, pH, and soil texture. Three species of wood-feeding termites were identified, including Globitermes sulphureus (47%), Microcerotermes crassus (32%), and M. distans (21%). The sizes of mounds were the largest for G. sulphureus, followed by M. crassus and M. distans. The characteristics of termite mound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Furthermore, the termite nests are also suitable for the growth of the genus Bacillus due to the pH of termite nests of have approximately neutral (pH range of 6.88 -7.38). Previous research also demonstrated that the pH values of from Globitermes sulphureus, Microcerotermes crassus and M. distans mound nests in Thailand were 6.99, 6.88 and 7.11, respectively [54]. Additionally, the pH 7.38 of Coptotermes formosanus mound nest was also found similarity in India [55].…”
Section: Bacterial Identificationmentioning
confidence: 76%
“…Furthermore, the termite nests are also suitable for the growth of the genus Bacillus due to the pH of termite nests of have approximately neutral (pH range of 6.88 -7.38). Previous research also demonstrated that the pH values of from Globitermes sulphureus, Microcerotermes crassus and M. distans mound nests in Thailand were 6.99, 6.88 and 7.11, respectively [54]. Additionally, the pH 7.38 of Coptotermes formosanus mound nest was also found similarity in India [55].…”
Section: Bacterial Identificationmentioning
confidence: 76%
“…Termites are swarming insects that build large mounds of earth to survive [3]. They build enormous mounds of earth to survive [4], the aboveground portion of which is called a termite mound, which often towers above the ground in the shape of a tower, column, or cone and can reach heights hundreds of times its own [5].…”
Section: Introductionmentioning
confidence: 99%